2021
DOI: 10.1101/2021.12.23.21268347
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ex-vivo mucolytic and anti-inflammatory activity of BromAc in tracheal aspirates from COVID-19

Abstract: COVID-19 is a lethal disease caused by the pandemic SARS-CoV-2, which continues to be a public health threat. COVID-19 is principally a respiratory disease and is often associated with sputum retention, for which there are limited therapeutic options. In this regard, we evaluated the use of BromAc, a combination of Bromelain and Acetylcysteine (NAC). Both drugs present mucolytic effect and have been studied to treat COVID-19. Therefore, we sought to examine the mucolytic, antiviral, and anti-inflammatory effe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Thus the combination therapy, BromAc, synergistically weakened the infectivity of SARS-CoV-2 cultured on Vero cells [166]. Further study indicated strong mucolytic and anti-inflammatory effect of BromAc ex vivo in tracheal aspirates from severe patients with COVID-19 [167]. Curcumin (diferuloylmethane) is a natural phenol found in turmeric (Curcuma longa), a member of the ginger family of plants [170].…”
Section: Combination Therapy With Biomacromolecule and Small Moleculementioning
confidence: 99%
“…Thus the combination therapy, BromAc, synergistically weakened the infectivity of SARS-CoV-2 cultured on Vero cells [166]. Further study indicated strong mucolytic and anti-inflammatory effect of BromAc ex vivo in tracheal aspirates from severe patients with COVID-19 [167]. Curcumin (diferuloylmethane) is a natural phenol found in turmeric (Curcuma longa), a member of the ginger family of plants [170].…”
Section: Combination Therapy With Biomacromolecule and Small Moleculementioning
confidence: 99%